Studies in bovine blood constituents in Wakwa. I. Haematological values - Salah, J.N.S.; Tanya, Y.N.; Mutia, F.M. (1984)
The blood contituents of Adamawa Gudali and Wakwa cattle were exaluated to determine the haematological values for each breed. The effects of sex and age on the parameters were also examined.